Aplikasi Metode HVSR pada Perhitungan Faktor Amplifikasi Tanah di Kota Semarang - Partono, Windu; Irsyam, Masyhur; Prabandiyani R.W., Sri; Maarif, Syamsul (MEDIA KOMUNIKASI TEKNIK SIPIL, 2013)
The Horizontal-to-Vertical Spectral Ratio (HVSR) is a simple method for estimating the resonance frequency of sedimentary layers. This method can also be used for estimating the site amplification factor. By using the resonance frequency and the amplification factor HVSR method can also be used for predicting the depth of the bed rock or the thickness of sediment layer (Nakamura, 1989). This paper presents results of HVSR method applied to ambient vibrations for estimating the amplification factor of sedimentary layer. A total of 16 ambient vibration measurements were performed in the City of Semarang to predict the amplification factor for the shallow sedimentary layers.